Searching for Dark Matter with the ^{229}Th Nuclear Lineshape from Laser Spectroscopy - Elina Fuchs; Fiona Kirk; Eric Madge; Chaitanya Paranjape; Ekkehard Peik; Gilad Perez; Wolfram Ratzinger; Johannes Tiedau (Physical Review X)
The recent laser excitation of the low-lying ^{229}Th isomer transition has started a revolution in ultralight dark matter searches. The enhanced sensitivity of this transition to the large class of dark matter models dominantly coupling to quarks and gluons will ultimately allow us to probe coupling strengths 8 orders of magnitude smaller than the current bounds from optical atomic clocks, which are mainly sensitive to dark matter couplings to electrons and photons. We argue that, with increasing precision, observations of the ^{229}Th excitation spectrum will soon give the world-leading constraints. Using data from the pioneering laser excitation of ^{229}Th by Tiedau et al. [Phys. Rev. Lett. 132, 182501 (2024)PRLTAO0031-900710.1103/PhysRevLett.132.182501], we present a first dark matter search in the excitation spectrum. While the exclusion limits of our detailed study of the lineshape are still below the sensitivity of currently operating clock experiments, we project the measurement of Zhang et al. [Nature (London) 633, 63 (2024)NATUAS0028-083610.1038/s41586-024-07839-6] to surpass it.